Autophagy activation by dietary piceatannol enhances the efficacy of immunogenic chemotherapy - Wang, Shuang; Wang, Guangsuo; Wu, Weiqing; Xu, Zhenglei; Yang, Jing; Cao, Min; Wang, Qi; Wang, Jigang; Yang, Chuanbin; Zhang, Wei (Frontiers in Immunology, 2022)
Immunogenic cell death (ICD) promotes the immune antitumor response via releasing damage-associated molecular patterns (DAMPs) from dying tumor cells. The induction of autophagy improves the efficacy of multiple immunogenic chemotherapies. Here, we showed that piceatannol, a dietary phenolic compound that is widely distributed in multiple fruits and vegetables such as grapes, blueberries, and mushrooms, induces autophagy and enhances oxaliplatin (OXA)-induced anticancer immune response. Specifically, piceatannol enhanced the OXA-induced release of DAMPs several key hallmarks of ICD including ATP release, cell surface exposure of calreticulin, and high-mobility group box 1 (HMGB1) release. Mechanistically, piceatannol promoted autophagy via activating TFEB/TFE3, two key transcriptional factors for the autophagy-lysosome pathway, and inhibiting autophagy attenuated piceatannol plus OXA-induced ATP release. Furthermore, piceatannol induced endoplasmic reticulum stress, which is critical for its role in enhancing OXA-induced cell surface exposure of calreticulin, another key hallmark of ICD. Consistently, the combination of piceatannol with OXA promoted anticancer effects in immunocompetent mice. Taken together, our results indicate the importance and great potential of dietary piceatannol in cancer immunotherapy. Therefore, piceatannol may be used as an ICD enhancer that improves the efficacy of chemotherapeutics such as OXA in cancer treatment with minimized toxicity.